Faktor-Faktor Yang Mempengaruhi Rendahnya Dalam Penggunaan Alat Kontrasepsi Pil Pada Pasangan Usia Subur (PUS) Di Puskesmas Bies Kecamatan Bies Kabupaten Aceh Tengah - Febriyanti, Selvia; HS, Nurlaely; Zulfikar, Zulfikar (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Family Planning is an effort to increase community awareness and participation through maturing marriage, birth control, fostering, family resilience, improving family welfare, to create a happy and prosperous small family. The purpose of this study is to identify and analyze the factors that influence the low use of contraceptive pills among couples of childbearing age (PUS). The benefit of this study is to increase insight into the factors that influence the low use of contraceptive pills among couples of childbearing age at the BIES Community Health Center. This type of research uses quantitative research with a cross-sectional research design. The location of the study is the Bies Community Health Center, the research period is from May to July 2025. The population in this study are all couples of childbearing age (PUS) who use contraceptives totaling 1,085 respondents. The sample taken using probability sampling technique, with the number of samples in this study amounting to 92 PUS mothers. The analysis used is the chi-square test (a = 0.05). The results of the chi-square test showed that there was a relationship between knowledge of the use of contraceptive pills with the value (p-value = 0.000 <0.05), there was a relationship between the mother's attitude towards the use of contraceptive pills with the value (p-value = 0.002 <0.05), there was a relationship between husband's support for the use of contraceptive pills with the value (p-value = 0.001 <0.05), there was no relationship between the mother's education on the use of contraceptive pills with the value (p-value = 0.648 >0.05). Suggestions for PUS mothers to pay more attention to the benefits, advantages, and side effects in determining the type of contraception to be used.